Benefits and costs of connecting logistics enterprises to digital logistics platforms. The perspective of transaction costs theory - Niemczyk, Jerzy; Szala, Paulina (Korzyści i koszty zmiany związanej z wchodzeniem przedsiębiorstwa logistycznego do cyfrowych platform technologicznych. Perspektywa teorii kosztów transakcyjnych, 2021)
Objective. The research aims to verify the profitability of the change consisting in the transition of a logistics company from the structures of hierarchical solutions requiring the expansion of its own transport order collection system, to structures using a digital logistics platform delivered by a specialized company based on a specific contract. Within the conducted research, the authors used a critical review of the literature on the subject, realized desk research and case study analyses. The obtained results confirm the advantage of moving from hierarchical structures that require expanding one’s own transport order collection system, to structures using a digital logistics platform of a specialized company, based on a periodic contract with network distinguishing characteristics. The obtained results will be used as the basis for further research on the possibilities of analysing organizational management systems based on the contracting models of digital logistics platforms. The research results will broaden the knowledge on the interpretation of the advantages of digital logistics platforms from the perspective of the transaction costs theory
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 1 (59), s. 81-99
Keywords: logistics; digital technology platforms; digital logistics platforms; transaction costs theory; logistyka; platformy technologii cyfrowych; cyfrowe platformy logistyczne; teoria kosztów transakcyjnych